The Marketing Efficiency Development to Create Value-Added for Product and Service of Community-Based Tourism. Study Case for Phatthalung Province - NA SONGKHLA, Ratirath; WANVIJIT, Wit; CHAROENBOON, Pawintana; NINAROON, Panida (Journal of Environmental Management and Tourism, 2021)
This study aims to examine the hypothesis and to carry out the path analysis of casual relationship influencing the marketing efficiency development to create value-added for product and service of community-based tourism; Phatthalung Province, Thailand. The findings are as follows. First, the hypothesis model matched with the empirical data by considering the value of CMIN/df = 1.596, p-value = .768, GFI = .976, AGFI = 0.972. RMR = 0.000, RMSEA = 0.005, NFI = 0.991, TLI = 0.998 and CFI = 0.999, respectively. The total effect of the causal variable having most effect towards the marketing efficiency development is the entrepreneurial orientation and all compositions explained the marketing efficiency’ s variance accounting for 71.90%. Second, the conceptual model of the causal relationship having effect towards the marketing efficiency development consists of one direct effect variable – the entrepreneurial orientation whereas there are 3 direct and indirect effect variables having effect towards the marketing competency; risk appetite, proactive operation and innovation capability.